Emulated reactance and resistance by a SSSC incorporating energy storage device - H. V. Gururaja Rao; Nagesh Prabhu; R. C. Mala (Institute of Advanced Engineering and Science, 2019)
Static Synchronous series compensator without energy storage device can exchange only reactive power with the network and can operate in limited operating range in two quadrants only. When energy storage device is connected at the DC bus of SSSC (SSSC – ES), it can also exchange real power with the network. Operating range of SSSC will be much broader and it covers all the four quadrants. However, emulated reactance and resistance by SSSC – ES is likely to affect the performance of a distance protection system. This paper presents a detailed model of an SMIB system with SSSC – ES. Injected voltage by SSSC – ES in all the four quadrants of operation is presented. Impact of operation of SSSC _ ES in different quadrants and various control strategies for SSSC – ES on impedance emulated by SSSC – ES during steady state condition and transient system disturbance is discussed.